The Psychological Impacts of COVID-19 Home Confinement and Physical Activity: A Structural Equation Model Analysis - Sang, Xuehui; Menhas, Rashid; Saqib, Zulkaif Ahmed; Mahmood, Sajid; Weng, Yu; Khurshid, Sumaira; Iqbal, Waseem; Shahzad, Babar (Frontiers in Psychology, 2021)
Background COVID-19 break out has created panic and fear in society. A strict kind of lockdown was imposed in Wuhan, Hubei province of China. During home confinement due to lockdown, people face multidimensional issues. The present study explored the psychological impacts of COVID-19 home confinement during the lockdown period and Wuhan’s residents’ attitude toward physical activity. Methods A cross-sectional online survey was conducted to collect the primary data according to the study objectives. The population was Wuhan residents (+ 18 years) who were in home confinement. A total of 2280 participant’s reply to the online questionnaire survey and collected data after quantifying the data, about 2200 (96.49%); about (49.8%) female, about (49.4%) male, others about (0.2%), and about (0.6%) were not disclosed their gender participants responses were used for analysis. The collected data were analyzed through appropriate statistical techniques. Results According to results, H1 is supported with β = −40.793, t = 57.835, p = 0.000, which claimed a negative association between COVID-19 lockdown policy and behavior and attitude. Results for H2 reveals that the COVID-19 lockdown policy have negative influence on emotional control with β = −0.769, t = 46.766, p = 0.000 and it is supported. H3 documented a significant positive relationship between COVID-19 lockdown policy and lockdown period psychological impact, which means lockdown policy, is the main reason to increase the lockdown psychological impact. Further, COVID-19 lockdown policy have negative influence on physical activity (H4) and self-belief (H5) with β = −0.657, t = 32.766, p = 0.000 and β = −0.620, t = −6.766, p = 0.000 respectively. H6 stated that there is a positive impact of behavior and attitude toward physical activity. The results for H6, behavior, and attitude affecting the physical activity with β = 0.401, t = 10, p = 0.000, which is supported. Conclusion COVID-19 home confinement created various psychological impacts, negatively affecting the emotional state due to depression and anxiety. Physical activity is the best strategy to manage human nature’s psychological issues, and people’s attitudes were positive toward physical activity during home confinement. However, the lockdown policy also affects physical activity participation negatively, and a sedentary lifestyle prevailed during home confinement.